Efektivitas Pelaksanaan Program Pelayanan Publik Plus di Kecamatan Kuranji Kota Padang - Arni Eka Susantri (Faculty of Social Science, Universitas Negeri Padang, 2018)
The purpose of this study was to describe the effectiveness of the implementation of “public service plus” programs in Kecamatan Kuranji Padang City. This study described the effectiveness of program implementation seen from the quality of apparatus, administrator competence, facilities and infrastructure, discipline, and supervision. This study was a descriptive research with quantitative approach. The population of this study amounted to 1285 users of public services plus, with a sample of 93 respondents determined by Slovin formula and used random sampling technique. Instrument in this study used questionnaire with Likert scale measurement. Data in this study were analyzed with descriptive statistic. The results of this study indicated that the effectiveness of the implementation of public service plus programs only reached 49.7% and categorized as quite effective. In terms of effectiveness of the implementation of public service programs plus seen from the quality of apparatus, administrator competence, facilities and infrastructure, discipline and supervision, the service program only reached 57.3% and categorized as quite effective.